(untitled) (The Harvest, 2024)
The current debate on migration and development focuses on utilizing social and economic remittances, and adopting a co-development approach to promote development through migration. In Nepal, after the 2015 earthquake, many returnees and migrant households are struggling with poverty and feel compelled to migrate again. Additionally, people often aspire to migrate without being fully prepared for migrant life. This study aims to analyze the impacts of diaspora strategies on the longterm development of international labor migrants, aspiring migrants, returnees, and migrant households. An ethnographic qualitative research study was conducted in Sindhupalchowk district in 2016 to gain a deeper understanding of this phenomenon from the perspective of actors at the micro, meso, and macro levels. Empirical data was analyzed using the symbolic interactionism approach and narrative analysis, which helped understand how these actors interpret their experiences before and after migration. To discuss the economic aspects of migration, the Neoclassical theory (Borjas) has been applied, while to discuss sociological aspects and transnationality, the Migrant network theory and transnationalism perspective (Fiast, Fauser, Reisenauer) together with Peggy Levitt’s concept of social remittances have been applied. The study found that while the State views international labor migration as caused only by economic factors, transnationality has become a key factor at the micro and meso levels, influencing the social, familial, and economic transnational spheres of life of the actors. The study suggests that the State needs to view this phenomenon from a transnational perspective to address the sociological aspects and ensure the long-term development of international labor migrants, returnees, and migrant households.